Ceramics for oculo-orbital surgery. Issue 4 (May 2015) - Baino, Francesco; Vitale-Brovarone, Chiara
Abstract: Ceramics are an extremely versatile class of materials with an extraordinarily broad spectrum of applications, ranging from building industry to medicine. Ceramics began to be systematically investigated as implantable biomaterials in the 1950s and soon revealed surprising properties. Orthopaedics and dentistry are the preferred areas of surgical applications of ceramics, due to their suitable strength for load-bearing applications, wear resistance ( e.g. alumina and alumina/zirconia composites) and, in some cases, bone-bonding ability ( e.g. hydroxyapatite and bioactive glasses). Another clinical field where ceramics are playing a significant role is oculo-orbital surgery, a highly interdisciplinary medical area that focuses on the management of injured eye orbit, with particular regard to the repair of orbital floor/wall fractures and/or the placement of orbital implants after removal of a diseased eye. Especially in the latter case, implants are not intended for bone repair but have to be biointegrated in soft ocular tissues; therefore, suitable ceramics for this application are required to go beyond the "traditional" bone-bonding ability. This article provides a picture of the currently-used ceramics for such applications and explores new emerging perspectives, highlighting the promises for the future disclosed by the recent advances in nanobioceramics science.